Kidney disease impact on family survival of a sick person in Sri Lanka - A. Shashini Warnakulasooriya (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: In the mid-1990s, kidney disease was first reported from the Padaviya area; today, it is widespread throughout the dry zone. Most of those who fall income to this disease are farmers from economically disadvantaged communities. Consequently, the question of